Historical, philosophical, and legal foundations of education - Duka, Cecilio D. (Quezon City, Philippines : Phoenix Publishing House, Inc., 1997)
No one knows exactly where, when, and how education started, and why it started. And no one dares to object that education is of supreme importance in the life of every human being. It is an imperative fact that without food, we cannot survive. Without language, no culture will exist and without culture, no nation will thrive. Without education, the culture of nation will never be propagated nor transmitted to posterity.
Part One. Historical foundations of education -- 1. The Educational systems of ancient civilization -- 2. Education during medieval times -- 3. Movements that helped shape modern educational thoughts and ideas -- Part Two. Philosophical foundation of education -- 4. Philosophy and Education -- Part Three. Legal foundations of education -- 5. The Legal bases of Philippine educational system -- 6. The Philippine educational system and the department of education, culture and sports -- 7. The Curricula of Philippine schools.
Includes bibliographical references and index.
Keywords: EDUCATION